Consolation in Philippians: philosophical sources and rhetorical strategy - Holloway, Paul A. (Monograph series / Society for New Testament Studies, 2001)
Acknowledgements; Abbreviations; Introduction; Part I. Literary and Rhetorical Contexts: 1. The integrity of Philippians; 2. The rhetorical situation of Philippians; 3. On the genre of Philippians: ancient consolation; Part II. Consolation in Philippians: 4. Paul's consolatory strategy: discerning the things that matter (Phil. 1:3-11); 5. Discerning the things that matter in the gospel mission (Phil. 1:12-2:30); 6. Discerning the one thing that matters in the Christian life (Phil. 3:1-4:1); 7. Concluding parenesis, consolation and thank-you note (Phil. 4:2-23); Conclusion: an analysis of Philippians; Bibliography; Index of modern authors; Index of passages cited.